Asistensi Relawan Pajak Dalam Meningkatkan Kepatuhan Wajib Pajak Orang Pribadi Di Tax Center STIE Persada Bunda Tahun 2024 - Jusmarni; Deviana Sofyan; Asepma Hygi Prihastuti; Annesa Adriyani; Dodi Agusra; Irsyadi Zain; Y Rahmat Akbar; Tat Marlina; A'ang Chaarnaillan (CV. Multi Kreasi Media, 2024)
Taxes are mandatory levies which are one of the sources of state income which will be used for the development of the country and society based on applicable laws. A tax volunteer is someone who voluntarily contributes their time, energy, thoughts and expertise to play an active role in tax education activities. Tax volunteer assistance is one of the programs initiated by the Directorate General of Taxes (DJP) of the Ministry of Finance of the Republic of Indonesia in order to increase taxpayer compliance in carrying out their tax obligations. A tax center is an institution at a university that functions as a center for study, education, training and socialization of taxation to the campus environment, taxpayers and the community independently. This activity is a form of joint agreement program between the Directorate General of Taxes, Riau Regional Office and the Persada Bunda College of Economics.